Hoyeraal-Hreidarsson Syndrome Due to PARN Mutations: Fourteen Years of Follow-up - Burris, Ashley M. (Pediatr Neurol, 2015)
INTRODUCTION: Hoyeraal-Hreidarsson syndrome is a dyskeratosis congenita-related telomere biology disorder that presents in infancy with intrauterine growth retardation immunodeficiency, and cerebellar hypoplasia in addition to the triad of nail dysplasia, skin pigmentation, and oral leukoplakia. Patients with Hoyeraal-Hreidarsson syndrome often develop bone marrow failure in early childhood. Germline mutations in DKC1, TERT, TINF2, RTEL1, ACD, and PARN cause about 60% of Hoyeraal-Hreidarsson syndrome cases. CASE REPORT: We report 14 years of follow-up for a patient with Hoyeraal-Hreidarsson syndrome who initially presented as an infant with intrauterine growth retardation, microcephaly, and central nervous system calcifications. He was diagnosed with Hoyeraal-Hreidarsson syndrome at age six and had a complicated medical history including severe developmental delay, cerebellar hypoplasia, esophageal and urethral stenosis, hip avascular necrosis, immunodeficiency, and bone marrow failure evolving to myelodysplastic syndrome requiring hematopoietic cell transplantation at age 14. He had progressive skin pigmentation changes, oral leukoplakia, and nail dysplasia leading to anonychia. Whole exome sequencing identified novel biallelic variants in PARN. CONCLUSIONS: This case illustrates that the constellation of IUGR, central nervous system calcifications, and cerebellar hypoplasia, esophageal or urethral stenosis, and cytopenias, in the absence of congenital infection, may be due to Hoyeraal-Hreidarsson syndrome. Early diagnosis of Hoyeraal-Hreidarsson syndrome is important to optimize medical management and provide genetic counseling.